2470. The Effect of Information–Motivation–Behavioral Skills Model-Based Continuing Medical Education on Pediatric Influenza Immunization Uptake: A Randomized, Controlled Trial. (26th November 2018) - Fisher, William; Yaremko, John; Brown, Vivien; Garfield, Hartley; Rampakakis, Emmanuouil; Boikos, Constantina; Mansi, James A
Abstract: Background: Seasonal vaccination against influenza is the most important public health strategy to prevent influenza morbidity and mortality in children 6–23 months of age. However, influenza immunization uptake in this population remains sub-optimal. While parents look to healthcare professionals (HCPs) for guidance, HCPs may be neither aware of the burden of influenza disease in infants nor familiar with ways to address parental influenza vaccine hesitancy. The objective of this research was to describe the impact of an Information—Motivation—Behavioral Skills model (IMB)-based, accredited, online Continuing Medical Education (CME) program on seasonal influenza vaccination in children 6–23 months of age in Ontario, Canada during the 2016/2017 influenza season. Methods: A multi-center, randomized, controlled trial was conducted whereby HCPs were randomized to either an accredited IMB-based CME or to routine practice (no CME). The CME addressed influenza burden in young children and identified parental barriers (hesitancy) to influenza vaccination, designed to inform, motivate, and upskill HCPs. All vaccine options were reviewed, including the adjuvanted, trivalent, inactive, influenza vaccine (aTIV). Immunization rates were compared between groups using Pearson's chi-squared and a logistic regression model adjusting for socioeconomic status at the clinic-level. Results: A total of 68 HCPs were recruited: 33 randomized to the CME group and 35 to routine practice. HCP interactions with parents were evaluated during 628 visits: 292 visits by HCPs in the CME group and 336 by HCPs in the routine practice group. Parents seen by HCPs in the CME group were ~30% more likely to agree to immunize their child with seasonal influenza vaccination compared with parents seen by HCPs in the control group ( P = 0.007). The adjusted odds of influenza immunization were 1.5 times higher in the CME group compared with the control group. Children in the CME group were ~20% more likely to receive aTIV compared with children in the control group ( P < 0.001). Conclusion: HCP education with a tailored health behavior uptake model based CME addressing the burden of influenza disease in young children and influenza vaccine hesitancy was associated with a significant increase in influenza immunization. Disclosures: W. Fisher, Seqirus: Consultant and Investigator, Consulting fee and Speaker honorarium. J. Yaremko, Seqirus: Collaborator and Investigator, Speaker honorarium. V. Brown, Seqirus: Investigator, Speaker honorarium. H. Garfield, Seqirus: Investigator, Speaker honorarium. E. Rampakakis, Seqirus: Independent Contractor, Consulting fee. C. Boikos, Seqirus: Employee, Salary. J. A. Mansi, Seqirus: Employee and Shareholder, Salary.